The Letter as Object. The Written Word between Reification and Hermeneutics in Rabbinic Judaism - Madalina Vârtejanu-Joubert (Cahiers Mondes Anciens)
My attempt is to answer the question of “the pragmatic contexts within which the authority of writing is established”. This authority is double in the case of Judaism as what is “written” and, starting with a particular moment in history, as the act of “writing”. Starting with the Second Temple, the Torah is sacred as “word” and “scroll” at the same time as it is sacred by means of its content and as an object. The history of Judaism will be constantly characterized by this double simultaneous sacredness. According to the scholar literature, this phenomenon has been unique in the Mediterranean and Middle Eastern worlds ever since the end of Antiquity. At the time, two new book cultures were born almost simultaneously: that of emergent Christianity and that of Judaism in change. I think that drawing attention to this novelty will help us to one day explain this phenomenon, even if at present there is no hypothesis in relation to Judaism. The rationalisation of this double sacredness in the rabbinical texts consists in the hermeneutical valorisation of material aspects. But, on the other hand, the hermeneutical enterprise makes use of procedures for the reification of writing; hence ensue a whole array of discussions on the form of letters and the meaning of that form. We are witnessing there a double phenomenon : the “textualisation” of reality and the “reification” of the text.